Image vectorization using optimized gradient meshes - Sun, Jian; Liang, Lin; Wen, Fang; Shum, Heung-Yeung
Recently, gradient meshes have been introduced as a powerful vector graphics representation to draw multicolored mesh objects with smooth transitions. Using tools from Abode Illustrator and Corel CorelDraw, a user can manually create gradient meshes even for photo-realistic vector arts, which can be further edited, stylized and animated. In this paper, we present an easy-to-use interactive tool, called optimized gradient mesh, to semi-automatically and quickly create gradient meshes from a raster image. We obtain the optimized gradient mesh by formulating an energy minimization problem. The user can also interactively specify a few vector lines to guide the mesh generation. The resulting optimized gradient mesh is an editable and scalable mesh that otherwise would have taken many hours for a user to manually create.